One-Pot Conversion of Fluorophores to Phosphorophores - Soll, Matan; Sudhakar, Kolanu; Fridman, Natalia; Müller, Alexander; Röder, Beate; Gross, Zeev (Organic letters, 2016)
Facile, one-pot conversion of free base 5,10,15-tris(pentafluorophenyl)corrole, (H3)tpfc, into the coinage metal complexes of 2,3,17,18-tetraiodo-5,10,15-tris(pentafluorophenyl)corrole, (I4-tpfc)M (M = Cu, Ag, Au), is reported. The iodination/metalation procedures provide much higher yields and larger selectivity than both conceivable stepwise syntheses. Photophysical analysis shows that the gold(III) complex (I4-tpfc)Au displays phosphorescence at room temperature and a substantial quantum yield for singlet oxygen formation.